A Commentary on Social Media Research From the Perspective of a Sport Communication Journal Editor. (June 2014) - Pedersen, Paul M.
This Twitter Research Forum essay by International Journal of Sport Communication (IJSC) Editor and leading strategic sport media scholar Paul Pedersen provides an important perspective on the challenges encountered by scholarly journals to the rise of interest in social media and sport. Using metrics on the content of articles published in IJSC, Pedersen notes publications concerning social media and sport have now reached parity with research on legacy media in electronic and print forms. Pedersen observes that because social media data are often readily available, scholars can quickly produce social media thematic/content analyses and surveys and that these are less taxing and time consuming when compared to other methods appropriate to studying other topics. This has resulted in a seeming avalanche of social media and sport submissions and raises questions about whether journals focused exclusively on digital media and sport are needed. The rise in submissions has presented challenges in selecting appropriate reviewers and raised risks of an academic groupthink within delimited quarters of the sport communication academic community. The essay closes with suggestions for research on sport and social media to advance its agenda to inquiry that is more innovative, rigorous, substantive, and significant.